Efektivitas Layanan Konseling Kelompok Dengan Teknik Self-Instruction Untuk Mengurangi Burnout Akademik - Palenza, Nabila Rezky; F, Firman; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Academic burnout is a condition of emotional exhaustion, cynicism towards learning tasks, and decreased academic efficacy that impacts student performance. One effective intervention that can be done is group counseling services with self-instruction techniques. This study aims to review the effectiveness of this technique in reducing academic burnout through a literature study approach. Analysis was conducted on various scientific literature from accredited national journals and relevant theses. The results of the study indicate that self-instruction techniques applied in group counseling are effective in significantly reducing academic burnout levels. This technique helps students change negative internal dialogue into positive ones, thereby increasing learning motivation and self-efficacy. This study recommends the implementation of self-instruction-based group counseling as an alternative intervention in educational environments.